Characteristics and transcatheter closure of patent ductus arteriosus in patients living at moderate to high altitude in Eastern Anatolia - Serdar Epçaçan; Mustafa Orhan Bulut; Yüksel Kaya; Ilker Kemal Yücel; Çayan Çakır; Emrah Şişli; Yemlihan Ceylan; Ahmet Çelebi (KARE Publishing, 2019)
Objective: The incidence of patent ductus arteriosus (PDA) is greater among patients living at high altitude. In this po-pulation, the ductal diameter is often larger and pulmonary hypertension is more frequent. The aim of this study was to evaluate the hemodynamic and morphological features of PDA and transcatheter closure procedures performed with various devices in a group of patients living at high altitude in Turkey. Methods: The data of 327 patients who lived at an altitude of at least 1600 m above sea level and who had undergone cardiac catheterization for isolated PDA between May 2010 and July 2018 were retrospectively analyzed. Results: The mean age was 7.33+-7.67 years, and 62.4% of the patients were female. The mean ductal diameter was 3.74+-2.14 mm. Pulmonary hypertension was present in 57.8%. Transcatheter closure was performed in 322 patients, with a 97.3% success rate. The Amplatzer duct occluder I (ADO I) was used most often, as well as off-label use of the Amplatzer vascular plug II (AVP) and the Amplatzer muscular ventricular septal defect occluder (AMVSDO). Pulmonary artery pressure decreased immediately in the vast majority after percutaneous closure. Transient left ventricular systolic dysfunction after ductal closure was seen only rarely. Follow-up was uneventful. Conclusion: Transcatheter PDA closure can be performed with high success rate in highlanders. Off-label devices may be required for these procedures. Pulmonary hypertension is frequent but regresses after ductal closure. Transient left ventricular dysfunction after transcatheter closure is rarely seen in these patients and resolves without any medication.